ANALISIS PEMETAAN PERSEPSI CITY CAR MELALUI MULTI DIMENSIONAL SCALING PADA STUDI KASUS PERSAINGAN KENDARAAN CITY CAR DI SURABAYA - Johnny Hadi Raharjo (Media Mahardhika, 2022)
This study aims to determine the position of the City Car product of Toyota Yaris with competing products based on consumer perceptions of product attributes. The method used is quantitative. approach, which in this study used perceptual mapping with an assessment based on attributes among several brands that compete with the Toyota Yaris. Data collection is done by assigning the students S1 all Surabaya's University,. Data from the Questionnaire in the MDS analysis showed that the product of the Toyota Yaris only has an advantage in the resale price of 16 attributes. City Car compared to other competing products.